2019
DOI: 10.1002/ecs2.2884
|View full text |Cite|
|
Sign up to set email alerts
|

Multiscale habitat mediates pest reduction by birds in an intensive agricultural region

Abstract: Habitat augmentation on farms is predicted to conserve biological diversity and support beneficial animals that reduce crop pests. Effectiveness of local habitat enhancement and subsequent pest reduction services can be mediated by the amount of habitat at larger scales. We tested whether the presence and increase of local and landscape scale bird habitat increased avian predator abundance and pest reduction by birds. We surveyed birds and performed a sentinel prey exclosure experiment in walnut orchards in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 138 publications
0
13
0
Order By: Relevance
“…insectivorous birds and ants) that can affect the diversity of termites. Research by Heath and Long (2019) revealed that the predation of insectivorous birds increased with an increasing area of semi-natural habitat in orchards. This is related to the needs of insectivorous birds to consume a lot of insects (Nyffeler et al 2018).…”
Section: Effect Of Habitat Characteristics On Ants and Termitesmentioning
confidence: 99%
“…insectivorous birds and ants) that can affect the diversity of termites. Research by Heath and Long (2019) revealed that the predation of insectivorous birds increased with an increasing area of semi-natural habitat in orchards. This is related to the needs of insectivorous birds to consume a lot of insects (Nyffeler et al 2018).…”
Section: Effect Of Habitat Characteristics On Ants and Termitesmentioning
confidence: 99%
“…2016, Kaiser‐Bunbury et al. 2017, Heath and Long 2019). The management of multifunctional landscapes should therefore target at benefiting service‐providing organisms to enhance the flow, stability and resilience of ecosystem services supporting production (Doré et al.…”
Section: Introductionmentioning
confidence: 99%
“…Landscapes providing multiple products and services (i.e., multifunctional) are key to combine food security and biodiversity conservation worldwide, as they integrate human activities with the preservation of ecosystem structure and function Merenlender 2018, Manning et al 2018). In such landscapes, biodiversity contributes to food and fiber production, and to reduce its negative environmental externalities, by providing critical services such as pollination and pest control (Mace et al 2012, Maas et al 2016, Kaiser-Bunbury et al 2017, Heath and Long 2019. The management of multifunctional landscapes should therefore target at benefiting service-providing organisms to enhance the flow, stability and resilience of ecosystem services supporting production (Dor e et al 2011, Bommarco et al 2013, Tittonell 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In sunflower fields, hedgerows reduced damage to sunflower seeds from sunflower moths below the economic threshold for pesticide use without increasing damage due to pest birds [ 33 ]. However, in walnut orchards, hedgerows increased bird predator without control of codling moth, probably because walnut orchards themselves supported the presence of the two woodpecker species that controlled the moth [ 38 ]. Similarly for pollination services, hedgerows increased seed set provided by native bees for potted canola in a sentinel experiment, but had no effect on sunflower seed set at the field scale [ 39 , 40 ].…”
Section: Case Studiesmentioning
confidence: 99%